TREATMENT FOR CHRONIC HEART FAILURE IN ELDERLY SUBJECTS - A. S. Poskrebysheva; N. A. Shostak; E. S. Trofimov (Klinicist, 2014)
The treatment of chronic heart failure (CHF) in patients over 60 years of age may be a challenge to a general practitioner. The physiological features of the elderly and significant comorbidity frequently have a considerable impact on the effects of drugs and the magnitude of side effects. Reduced sinus node automatism, significant atherosclerosis of the aorta and great vessels, and renal dysfunction - all should be borne in mind when choosing a drug and its dosage regimen. The paper considers non-drug treatment modalities, as well as the specific features of use of some groups of drugs and therapy for concomitant diseases in elderly patients with CHF.